Kinetic profile and incidence of injuries among high performance trampoline gymnasts - Kuisis, S. M.; Camacho, T.C.; Dafel, S. M.; van Rensburg, D. C. J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was: a) Determine the differences among injured and noninjured trampolinists with regard to kinetic data collected; b) Determine if there were any associations between the type of injuries sustained and the kinetic data collected. A one year retrospective analysis of kinetic test results and medical records of a group of high performance trampolinists was performed. Fifteen participants between the ages of 10-20 participated in the study (9 males and 6 females). 40% of participants sustained an injury for which they sought medical advice. The incidence of injury per 1000hours of trampoline use was 2.3. Injured trampoline gymnasts had significantly lower range of motion of the left ankle and total work values for the left dorsiflexors. Coaches, gymnasts and parents should be educated about the potential risks and take measures in preventing injuries.